Half Empty? Drinking Water Systems and Regional Resilience in Rural Canada. (15th March 2019) - Breen, Sarah-Patricia; Markey, Sean
ABSTRACT: This paper investigates the extent that new regionalism has been employed in the planning of rural drinking water systems as a strategy to support rural regional resilience. Through a content analysis of policy documents, this paper explores the question of whether current approaches to the planning of rural drinking water systems reflect a transition towards regional resilience. While there is potential for drinking water systems to support or enhance rural regional resilience, this potential is emergent at best. Policy documents reveal the adoption of regionalist practices is challenged by a lack of regional cohesion and barriers from existing institutional structures.